Effect of probiotics in diarrhea and GE Reflux in pediatrics. - Yazdani, Alireza; Eslami, Kaveh; Peyvasteh, Mehran; safayee, farnaz (International Pharmacy Acta, 2018)
Probiotics are defined as nonpathogenic bacterial depravities (Lactobacillus GG Enterococcus faecium,Lactobacilus acidophilus & Bifidobacterium bifidum) that provides better ,and normal intestinal floral and function ,which balances Intestinal micro-organism and supports the immune system. One of the most common form of diarrhea is Antibiotic induced diarrhea, in which probiotics are used as preservative therapy. A significant number of patients with diarrhea are children (infant –toddler), who have underdeveloped immune system and diarrhea may cause life-threatening event. GE reflux is a common disease in infants. probiotics are now taking a part in the treatment of these children but it is not approved by FDA, although some surveys have shown its benefits. Introduction: The aim of this study is to see the role of probiotics in prevention and treatment of diarrhea and control of GE reflux, versus its high cost. Methods and Results: Four groups were studied in this analysis. The first group had diarrhea without probiotic treatment, the second group were patients with GE Reflux without probiotic treatment. The third group had diarrhea treated with probiotics, and the fourth group had GE reflux and were treated with probiotics. We used patients precise age, weight. variables were sex(female/male)age, (months), weight duration of disease with and without probiotics. In this study mean age was 24 months ,the minimum was 6 months and maximum was 78 months.58%of them were male and 42% were female. The mean treatment duration in group1 was 10 days. In third group was 7days which was reduced by 3 days. The mean treatment duration in group 2 was nearby 26 days. In third group was near 25 days. Conclusions: Probiotics have significantly reduced the duration of diarrhea but there has not been a prominent improvement in duration of disease in GE Reflux.